Study on an advanced borehole heat exchanger for ground source heat pump operating in volcanic island: Case study of Jeju island, South Korea - Kim, Jong Woo; Kim, Yeong-Min; Ko, Yoon Jung; Chen, Qian; Xin, Cui; Oh, Seung Jin (Frontiers in Built Environment, 2022)
This paper presents an advanced borehole heat exchanger that has been developed in order to apply a ground source heat pump to a volcanic island where the existing borehole heat exchangers are inapplicable by local ordinances. The advanced borehole heat exchanger was fabricated and installed at a verification-test site to evaluate its heat capacity in terms of refrigeration ton (RT). The proposed heat exchanger was also compared with the conventional heat exchanger that was made of HDPE heat exchanger. The thermal response test was carried out by flowing water at various temperatures into the heat exchangers at the fixed flow rate of 180L/min. The results revealed that the maximum heat capacity for the developed heat exchanger was measured at 63.9 kW, which is 160% higher than that of the HDPE heat exchanger (39.9kW). It was also found that the developed HX has the highest heat gain achieving 94 kW as compared to 21kW for HDPE-Hx.